Explorando a tecnologia ADSL: uma ferramenta de suporte ao ensino presencial e a distância - Caires, Juliette Gleide de Oliveira (2003)
The use of computer and Internet in support of education has reached great popularity. There is currently in Brasil a significant number of Universities and High Schools linked to computer networks. That proves the great interest of educational institutions in providing its students with a modern computational structure that allows that the pedagogical practices goes beyond the classroom. However, the interest of the educational institutions is not enough. The need for mechanisms that create an adequate, efficient and stimulanting learning environment through the Internet still remains. With the sprouting of faster Internet access technologies, known as broadband technologies, and modern tecniques that optimize the use of telecommunication channel, it is already possible to think about the use of multimedia resources (such as sound, image and video) in the support of education, mainly on those resources that promote a synchronous virtual interactivity between teacher and student. Therefore, it is important to study tools and resources that can be used to efficiently create the environments that allow this interaction. This way, the intention of this work is to consider and to evaluate Educational Sceneries that can use ADSL thecnology, the broadband thecnology more spread out currently in Brazil, and resources whch provide synchronous and asynchronous interactivity between teacher and students through the transmission of multimedia content through the Internet. The evaluation of the contexts is made through the measurement of the main quality of service (QoS) parameters obtained through practical experiments. Beyond the descriptions of the Educational Sceneries, topologies, used configurations, tools and the corresponnding performance evaluation, this work also presents the main technical characteristics of the ADSL thecnology, as well as tools which capture and distribute content multimedia through the Internet.